Shoulder replacement for osteoarthritis: A review of surgical management. (February 2018) - Pandya, Jay; Johnson, Tamara; Low, Adrian K.
Highlights: The incidence of shoulder arthroplasties is on the rise. Total shoulder arthroplasty is best indicated for patients with intact and functional rotator cuff and good glenoid bone stock. Reverse shoulder arthroplasty is indicated in older patients with associated cuff pathology. Although hemiarthroplasty rates are declining, it still has a role in younger patients (age < 50 years). Abstract: Osteoarthritis of the shoulder is caused by progressive cartilage wear of the glenohumeral joint. Its prevalence is increasing due to our ageing population and it may affect up to one-third of people over 60 years of age. Patients usually complain of pain with restricted shoulder movement and function. Initial treatment should be non-operative, such as activity modification, oral analgesics (e.g. non-steroidal anti-inflammatories) and possibly physical therapy or corticosteroid injections. Patients with ongoing severe pain and functional restriction despite non-operative treatment would be candidates for surgery, usually a shoulder replacement. There are various forms of shoulder replacements and the aim of this review is to discuss the types available, the indications for using one over another and recent worldwide trends in the use of shoulder replacements.